ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI PEMBELIAN IMPULSIF PADA PENGGUNA E-COMMERCE DI DKI JAKARTA - Resty Dwi Pratiwi, (2022)
This study uses a quantitative method with the aim of proving the effect of sales promotion, hedonic shopping value and self-control on impulsive purchases among e-commerce Phase 2 2022 Top Brand users, namely Tokopedia, Shopee and Lazada. This study used 100 respondents from users of Top Brand e-commerce Phase 2 2022 in DKI Jakarta as primary data, and secondary data researchers obtained through various references related to research. Data were collected using purposive sampling technique and analyzed using descriptive and inferential analysis techniques with the help of SmartPLS software. So that data processing obtains the results that (1) sales promotion has a significant positive effect on impulsive purchases (2) the value of hedonic shopping has a significant positive effect on impulsive purchases, (3) self-control has a significant negative effect on impulsive purchases.